Stepwise cluster ensemble downscaling for drought projection under climate change. (13th January 2023) - Wen, Yizhuo; Yang, Aili; Fan, Yurui; Wang, Bingqing; Scott, Daniel
Abstract: Drought is one of the most serious natural disasters exacerbated by climate change. Changes in precipitation and temperature in the future increase the likelihood of drought in China. In this study, a stepwise cluster ensemble downscaling (SCED) model was developed to bias‐correct projections of temperature and precipitation from multiple RCM outputs, and further characterized the drought hazards. The developed SCED model was used to aggregate and correct the results of multiple regional climate models, and its performance was proved to be reliable by comparing with the observed results. The proposed SCED method has been applied for drought projections over the Fujian province, China. The results showed that the changes of precipitation and temperature in Fujian would have obvious spatial heterogeneous characteristics. The temperature in the southeast coastal areas will increase by up to 4°C and the precipitation will decrease by 3.1% in the late 21st century, while the temperature rises and precipitation increases in the southwest. Temperature in inland areas will be lower and precipitation will be less. The drought hazards were also characterized by both SPI and SPEI based on biased‐corrected projections from SCED model. According to the SPI and SPEI indices, although the number of dry months in Fujian province will not change significantly in future, the spatial and temporal heterogeneity may become more explicit. Moreover, the moderate drought (from SPI) may increase while the general drought may decrease (from both SPI and SPEI). For extreme droughts, there would not be visible changes detected by SPI, but an increasing trend characterized since the impact of temperature was included in SPEI. In addition, there would be an increasing trend on drought when increasing temperature and precipitation occurred simultaneously. Abstract : A stepwise cluster ensemble downscaling model was proposed for climate bias‐correction. The model was adopted for climate projections from multiple RCM models. Drought occurrence was revealed by standardized precipitation index (SPI) and standardized precipitation evapotranspiration index (SPEI) based on the outputs of stepwise cluster ensemble downscaling (SCED). Drought projections over Fujian were generated under different RCPs. In the figure, framework of SCED.